Moulinages : patrimonialisations d’une étape méconnue de l’industrie soyeuse - Flore Vigné (In Situ)
The Ardèche department is often vaunted today for its attractive natural landscapes and its historic heritage, but it stands out in French industrial history for its production of thrown silk, accounting for half of national production during the nineteenth century. The thrown silk is obtained during a little-known intermediate stage in the industry, called ‘moulinage’ in French, silk-throwing, situated between ‘filature’, the spinning, or, more precisely, the reeling of raw silk from the cocoons, and weaving. The process gives twists to one or several threads of hard silk, making them hold together but also giving the silk a series of other qualities such as brilliance, resistance, elasticity, and so on. The work we undertook for our geography thesis on the territory of the natural regional park of the Ardèche Mountains tried to answer a simple question: what has become of this industrial heritage? Between disappearance and conceptualisation as heritage, between inventory notices and citizens initiatives, our article looks at different forms of interpretation and promotion. To begin with we examine the industrial heritage itself, both physical and intangible, observing this heritage in the light of its links with the surrounding rural environment. We then go on to an analysis of the situation and the uses to which the heritage is put today, in keeping with different territorial tendencies within the department. And we conclude by asking what particularities can be observed in the heritagisation processes at work.